A questão indígena no norte do Rio Grande do Sul: intrusão, reforma agrária e extinção de reservas - 1940-1968 - Silva, Gean Zimermann da (2016)
The north center region of the state of Rio Grande do Sul, during the 20th century, was an area of great expression of social movements, usually struggle for the land. The indigene issue, between the 1940 and 1960 decades, expressed well this reality. The governor Leonel Brizola, as well as his antecessors, Cordeiro de Farias, Walter Jobim and Ildo Meneghetti, practices the reduction of indigenous territories, fact which was the cause of many conflicts. We point out the period of Brizola‟s government (1959-1963), because, it was the one that, in a certain way, intensified this practice. To understand this process of indigenous lands expropriation, is necessary we analyze the previous period in the beginning of the 20th century, when immigrants‟ descendants, migrate from the colonial area of today's municipalities of São Leopoldo-RS and Caxias do Sul-RS to the colonies in north-central Rio Grande Also it is a period when the positivist government, demarcate 11 indigenous areas, among them, the Ventarra one, the empirical area of our study. From the 1940 decade, practically all the state‟s lands are occupied. However, there were landless settlers, and, from that, begins to occur social movements for the region. The intrusion in the indigenous areas culminates in a social movement, that is, by one side the landless settlers and on the other one, indigenous. A Parliamentary Investigation Committee (CPI) is established to investigate the settlement of settlers on indigenous areas, and especially the Nonoai one in 1967. Our analysis seeks to contemplate this effervescent period when the land issue in Rio Grande do Sul is involved; focus the analysis on processes of reduction and extinction of the indigenous area in Ventarra as condensation of a state policy on the period. We demonstrate that there was, between the years of 1940-60, a deliberate policy of turning indigenous territories into areas to relieve the tensions and conflicts for the land. The specific analysis of the Ventarra Reservation, demonstrates the mistake by part of this public policy, because beyond taking the indigenousterritories off and giving the settlers lands, produced new socials conflicts which currently extend themselves and reveal a hard resolution.